Frequency domain multiplexing readout for large arrays of transition-edge sensors - Vaccaro, Davide; Akamatsu, Hiroki; Gottardi, Luciano; van der Kuur, Jan; Nagayoshi, Kenichiro; Taralli, Emanuele; de Wit, Martin; Bruijn, Marcel P; Anton J van der Linden; Bert-Joost van Leeuwen; van der Hulst, Paul; Ravensberg, Kevin; et al. (arXiv.org, 2022)
We report our most recent progress and demonstration of a frequency domain multiplexing (FDM) readout technology for transition-edge sensor (TES) arrays, both of which we have been developing, in the framework of the X-IFU instrument on board the future Athena X-ray telescope. Using Ti/Au TES micro-calorimeters, high-Q LC filters and analog/digital electronics developed at SRON and low-noise two-stage SQUID amplifiers from VTT Finland, we demonstrated feasibility of our FDM readout technology, with the simultaneous readout of 37 pixels with an energy resolution at of 2.23 eV at an energy of 6 keV. We finally outline our plans for further scaling up and improving our technology.